The Problem of Education in Modern Pedagogy - Gulshoda, Juraeva (European Journal of Life Safety and Stability (2660-9630), 2021)
The problem of education is one of the most controversial in modern pedagogy. Despite the fact that we will find the chapter on upbringing in any textbook or manual on pedagogy, upbringing continues to be one of the most theoretically undeveloped pedagogical problems.